Effects of the Interculturality and Mindfulness Program (PIM) on University Students: A Quasi-Experimental Study - Roberto Chiodelli; Saúl Neves de Jesus; Luana Thereza Nesi de Mello; Ilana Andretta; Diana Fernandes Oliveira; Maria Emília Santos Costa; Tamara Russell (MDPI AG, 2022)
Rates of mental health issues have been increasing among university students. This study investigates the effects of the Interculturality and Mindfulness Program (PIM) on academic students on mindfulness, emotional regulation, depression, anxiety, stress, life satisfaction, optimism, positive solitude, and loneliness. A quasi-experimental research was conducted, with pre- and post-test comparative measurements in three groups: in-person (IG), synchronous online (OG), and passive control (CG). A diverse group of students (n = 150; mean age = 25.4 ± 8.31) participated from two universities in Portugal. When compared to the CG, both active groups (IG and OG) demonstrated a beneficial interaction effect in acceptance, positive solitude, optimism, and mindfulness. The IG demonstrated a positive interaction effect in awareness and satisfaction with life, whereas the OG indicated a favorable interaction effect in impulse. When analyzing the intra-group effects, both active groups presented a significant improvement in stress, emotion regulation, mindfulness, positive solitude, and optimism. The OG demonstrated an improvement in awareness and loneliness. The main limitations of this research are that students were not randomly assigned, and groups were heterogeneous in nationality, education level, and sex. Nonetheless, PIM has indicated beneficial results in both IG and OG, and is a promising intervention for the prevention of mental health issues (e.g., stress, difficulties in emotional regulation, and loneliness), as well as for the promotion of well-being (e.g., positive solitude, mindfulness, life satisfaction, and optimism).